2021
DOI: 10.24018/ejbmr.2021.6.6.1137
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transformational Leadership on Employee Performance: A Perspective of Employee Empowerment

Abstract: Critical literature review revealed that individualised consideration and intellectual stimulation factors of transformational leadership are the heart of employee empowerment. This study is important because there was little and discrete information on how individualised consideration and intellectual stimulation empower the performance of banking sector employees in the Dar es Salaam city. The study, therefore, examined the role of transformational leadership on employee performance based on employee empower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…Next, this study finds that employee performance is significantly improved by transformational leadership. This finding is in line with the previous study by Magasi (2021) who conducted research in the banking sector. He concluded that intellectual leadership is the heart of empowering employee performance and suggested that the most appropriate employee performance indicators are quality and reliable products, quality and reliable financial services, quality and reliable markets, quality and reliable technology, multiple products, portfolio, and effective feedback from customers.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Next, this study finds that employee performance is significantly improved by transformational leadership. This finding is in line with the previous study by Magasi (2021) who conducted research in the banking sector. He concluded that intellectual leadership is the heart of empowering employee performance and suggested that the most appropriate employee performance indicators are quality and reliable products, quality and reliable financial services, quality and reliable markets, quality and reliable technology, multiple products, portfolio, and effective feedback from customers.…”
Section: Discussionsupporting
confidence: 93%
“…According to Chen et al (2021), Tuzzakiyah et al (2021), Hassi (2018), andAndreani et al (2016), transformational leadership is positively connected to employee satisfaction via the mediating role of the experienced relationship climate perceived by employees. Further, Yucel (2021), Magasi (2021), Kimani (2021), Riyanto et al (2021), Farisi et al (2020), and Andreani et al (2016 all found significant results and a positive relationship between transformational leadership and employee satisfaction.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a similar vein, the literature supports that psychological trait such as creativeness, innovativeness, locus of control, self-efficacy, risk-taking propensity, passion, need for resilience, passion and tolerance for ambiguity, predict well the entrepreneurial orientations (Baron, 2000;(Bygrave, 1989;Sánchez, 2015). Similarly, Magasi (2021) asserts that creating new ideas, imagination, creativity, independent thinking and changing own ideas into products and reality are the foremost factors for competition-winning, organization's superior performance, and business sustainability. Barba-Sánchez and Atienza-Sahuquillo's (2018) findings also show that a strong need for independence is one of the most important factors for entrepreneurial intention.…”
Section: Is Entrepreneurship Education Alone Enough To Boost Entrepre...mentioning
confidence: 88%
“…Measuring the effectiveness of this leadership style is based on the degree of influence the leader has on employees Tajasom (2015) [14]. According to Khan, Anjam, Faiz and Khan (2020) [15] many leadership styles are related to increasing the performance of an organization. The level of job satisfaction is one of the key elements to measure performance in an organization.…”
Section: The Influence Of Leadership Style On Employee Performancementioning
confidence: 99%